Crank it up : Jason Statham: star! - Gerrard, Steven, 1970-; Shail, Robert (Manchester University Press, 2019)
Jason Statham has risen from street seller through championship diving and modelling to become arguably the biggest British male film star of the twenty-first century. This is the first book to offer a critical analysis of his work across a variety of media, including film, television, video games and music videos. Each chapter focuses on a particular aspect of Statham's career, from his distinctive screen presence to his style, branding and celebrity. Accessibly written, and featuring a contribution from Hollywood director Paul Feig, who worked with Statham on the 2015 action-comedy Spy , the collection will appeal to a wide audience of scholars, students and fans.